Pengawas an Pemilu Partisipatif dalam Mengawal Pemilu Tahun 2024 Yang Demokratis Didesa Sukaraja Kec. Lengkiti Kab. Ogan Komering Ulu - Apriana Satria Wira Darma; Destika Oktasari; Yuliza Arpita D.Y; Anja Widodo; Agung Pratama; Alip Susilowati Utama (Politeknik Kampar, 2023)
Simultaneous elections will be held on 14 February 2024 in all regions of Indonesia. However, the political and bureaucratic pathology that adorns the course of government in Indonesia is quite worrying, this is what causes strict supervision to prevent unwanted things from happening. Supervision is divided into two, the first is institutionalized supervision by Bawaslu and the community as the initial information provider. The targets for this activity were first-time voters, village officials and the general public, while the purpose of this activity was to educate the public to be aware of participatory supervision, with the Socialization Method and Focus Group Discussion (FGD) in practice, Pre Test and Post Test questions were also given to know the impact of the usefulness of the socialization carried out. The result of this activity is that the community is becoming more aware of and has increased their knowledge about participatory supervision for the 2024 general election by being active in society by asking about the obstacles it faces as participatory supervisors and responding to the efforts that can be made to resolve these obstacles